Hippocampal avoidance with volumetric modulated arc therapy in melanoma brain metastases – the first Australian experience - Awad, Raef (BioMed Central, 2013)
PURPOSE: Volumetric modulated arc therapy (VMAT) can deliver intensity modulated radiotherapy (IMRT) like dose distributions in a short time; this allows the expansion of IMRT treatments to palliative situations like brain metastases (BMs). VMAT can deliver whole brain radiotherapy (WBRT) with hippocampal avoidance and a simultaneous integrated boost (SIB) to achieve stereotactic radiotherapy (SRT) for BMs. This study is an audit of our experience in the treatment of brain metastases with VMAT in our institution. METHODS AND MATERIALS: Metastases were volumetrically contoured on fused diagnostic gadolinium enhanced T1 weighted MRI/planning CT images. Risk organs included hippocampus, optic nerve, optic chiasm, eye, and brain stem. The hippocampi were contoured manually as one paired organ with assistance from a neuroradiologist. WBRT and SIB were integrated into a single plan. RESULTS: Thirty patients with 73 BMs were treated between March 2010 and February 2012 with VMAT. Mean follow up time was 3.5 months. For 26 patients, BMs arose from primary melanoma and for the remaining four patients from non-small cell lung cancer (n= 2), primary breast cancer, and sarcoma. Mean age was 60 years. The male to female ratio was 2:1. Five patients were treated without hippocampal avoidance (HA) intent. The median WBRT dose was 31 Gy with a median SIB dose for BMs of 50 Gy, given over a median of 15 fractions. Mean values for BMs were as follows: GTV = 6.9 cc, PTV = 13.3 cc, conformity index = 8.6, homogeneity index = 1.06. Mean and maximum hippocampus dose was 20.4 Gy, and 32.4 Gy, respectively, in patients treated with HA intent. Mean VMAT treatment time from beam on to beam off for one fraction was 3.43 minutes, which compared to WBRT time of 1.3 minutes. Twenty out of 25 assessable lesions at the time of analysis were controlled. Treatment was well tolerated; grade 4 toxicity was reported in one patient. The median overall survival was 9.40 months CONCLUSIONS: VMAT for BMs is feasible, safe and associated with a similar survival times and toxicities to conventional SRT+/−WBRT. The advantage of VMAT is that WBRT and SRT can be delivered at the same time on one machine.